Impact of pharmaceutical teleconsultation on glycemic control of people with type 2 diabetes mellitus in a public pharmacy in Brazil: A randomized clinical trial protocol (TelePharmaceutical Care Diabetes Trial) – TPCDT - Gossenheimer, Agnes Nogueira; Alberti, Fernanda Fávero; Argoud, Vanessa Klimkowski; Gouvea, Diego da Silva; Preissler, Thales; Schneiders, Roberto Eduardo; Rigo, Ana Paula; Schaan, Beatriz D’Agord (Brazilian Journal of Science, 2023)
Telepharmacy is a fundamental tool to ensure glycemic control in patients who don’t access health services. The objective of this protocol is to report the procedures of a randomized clinical trial that will evaluate the impact and economic evaluation of a pharmaceutical teleconsultation service for patients using dapagliflozin, recently incorporated by the Brazilian public health system for the treatment of type 2 diabetes (T2D). Patients aged 65 years or older, with T2D, and who withdraw dapagliflozin in a public pharmacy located in southern Brazil will be recruited. They will be electronically randomized with allocation for intervention or control group. The intervention will be conducted out through three teleconsultations, one per month, with a pharmacist. The main outcomes will be glycemic control (hemoglobin A1c) and treatment adherence. Secondary outcomes will include lipid profile, blood pressure, and body mass index, number of hospital admissions, number of emergency room visits, number of medical consultations performed, number of problems related to pharmacotherapy identified and resolved, cost related to service and quality of life. The economic evaluation will be carried out using time-driven activity-based costing. Through this research, we will be able to identify whether pharmaceutical teleconsultation services can complement face-to-face consultations to improve health outcomes in T2D patients on dapagliflozin. The study was registered in Clinical Trials (NCT05380596).